If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-x-3=3-3-x
We move all terms to the left:
-x-3-(3-3-x)=0
We add all the numbers together, and all the variables
-x-(-1x)-3=0
We add all the numbers together, and all the variables
-1x-(-1x)-3=0
We get rid of parentheses
-1x+1x-3=0
We add all the numbers together, and all the variables
-3!=0
There is no solution for this equation
| (3/2)n-6=22;n | | 10.3w+14.84+9.2w=0.9w-18.64 | | 3(x+2)+4x−5=7(x+1)−6 | | 2+2/3t=1+1/4t | | (x−8)^2−6=43 | | 3(x−2)+1=3−(2−x) | | 4c=3c+c | | -7(4p-4)=84 | | 3-x/6=x/2 | | 6x+8x+1/4=38/3/4 | | 9+3x-1=2(x+5) | | -2(-3x+6)=-8x | | 14+5n=–4n+17 | | -16k+20=-14k-20 | | x−8(2−6=43 | | -8x-1+9x=-9x-7 | | X+6/2=x-1/2 | | 3/2x+2=1/2-1/2 | | 120+0.20m=70+0.40m | | 20+20-5j=-20-20j | | 2(-4x+2)=10x-6 | | 9x+5=8x=5 | | 4x-64+x=21 | | a/36=4/4 | | -4(5x-2)-2x-1=4 | | 3c-7/5=16 | | 14=5-3(r-2) | | 10s=8s-12 | | (4u+5)(6+-1u)=0 | | 12=-7-4(-8x+1) | | -13.2j-13.5=-3.4j+12.96 | | 5(x+2)−3=3x−8x+7 |